Patient-centered communication between adolescent and young adult cancer survivors and their healthcare providers: Identifying research gaps with a scoping review. Issue 2 (February 2018) - Gorman, Jessica R.; Standridge, Daniel; Lyons, Karen S.; Elliot, Diane L.; Winters-Stone, Kerri; Julian, Anne K.; Weprin, Jennifer; Storksdieck, Martin; Hayes-Lattin, Brandon
Highlights: Interventions explicitly evaluating AYA patient-centered communication are needed. There are no evidence-based interventions that improve these outcomes for AYA. Several promising approaches to improve patient-centered communication exist. Abstract: Objective: To conduct a scoping literature review to identify practices or programs that promote AYA patient-centered communication. Methods: Between January and May of 2016, we applied standard scoping review methodology to systematically review articles. We considered peer-reviewed, English language articles written at any phase of intervention research. Both qualitative and quantitative studies were eligible, and no additional search restrictions were applied. We retained articles that included explicit or implicit outcomes for one of the six functions of patient-centered communication in cancer care. At least two independent reviewers assessed the articles. Results: We screened a total of 4072 titles and abstracts, retaining 27 for full-text review. Ultimately, eight titles met the review's inclusion criteria. We categorized each publication by the action or setting used to improve patient-centered communication, resulting in five categories. Most studies were not included because they did not include a patient-centered communication outcome. Conclusion: This area of research is still emerging, as indicated by the small number of eligible studies and predominance of qualitative, descriptive, pilot, and feasibility studies with small sample sizes. Practice implications: Our results suggest a clear need to develop and evaluate interventions focused on improving patient-centered communication between AYA survivors and their healthcare providers.